Analisis Komparatif Kebijakan Pendidikan di Iran, Mesir, dan Turki: Ideologi, Reformasi, dan Tantangan Globalisasi - Zahra Albaturrizkiyah Lubis; Abdusima Nasution (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to analyze and compare educational policies in Iran, Egypt, and Turkey, three Muslim-majority countries with distinct ideological foundations and educational systems. Employing a library research method with a comparative approach, the study draws upon academic literature, policy documents, and previous research findings. The results indicate that Iran maintains a highly centralized education system characterized by a theocratic orientation and strong state control over curricula and higher education. Egypt adopts a dual educational structure that integrates the national secular system with the religious education system of Al-Azhar, seeking to balance modernization with the preservation of Islamic traditions. In contrast, Turkey emphasizes educational modernization through the development of twenty-first-century competencies, digital transformation, and the internationalization of higher education based on global standards. Despite their differing policy orientations, all three countries face similar challenges, including ensuring equitable access to education, improving educational quality, aligning educational outcomes with labor market demands, and responding effectively to the pressures of globalization. The findings further demonstrate that ideological orientations and political structures play a crucial role in shaping educational reforms and policy implementation within each country.